تدوير مخلفات مصانع االبلاستيك في عمل ألواح تغليف الجدران والسقوف عازلة للرطوبة والحرارة - دعد محمود داوود; نادية سالم اسماعيل (Journal of Engineering and Sustainable Development, 2010)
The work includes making concrete boards or panels used to cover walls from inside and false ceiling with dimension 200 * 200 * 30 mm , using Iraqi plastic factories wastes , by mixing it with cement , sand and water , using Polyvinyl Chloride and Acetate ( PVC ) to give panels high resistance for erosion , moisture and friction . Two mixes were used , first mixture (A)is 1 cement : 1 sand : 2 plastic wastes by size , the second mixture (B)is 1 cement : 2 sand : 3 plastic wastes by size . For the added material Polyvinyl Chloride and Acetate , many ratio were tried , the best ratio of this material to the weight of cement is 0.3 %. These boards were characterized by their high compressive strength; for the mixture (A ) is 13 MPa and for the mixture ( B ) is 8 MPa. The flexural strength for mix ( A )is 2.92 MPa while for mix ( B ) is 2.08 MPa, in addition to their good resistance to moisture, the percentage of absorption for mix ( A )is 2 % and for mix ( B ) is 3 %. Thermal insulation for mix ( A ) is 0.322 w/m2 c and for mix (B )is 0.375 w/m2 c , this is very good as compared with other materials used for coating. The other expected function of the production of these boards is the exploitation of various plastic factories’ wastes.